Updated Evaluation of Robotic- and Video-Assisted Thoracoscopic Lobectomy or Segmentectomy for Lung Cancer: A Systematic Review and Meta-Analysis - Zhang, Jianyong; Feng, Qingbo; Huang, Yanruo; Ouyang, Lanwei; Luo, Fengming (Frontiers in Oncology, 2022)
Objectives Robot-assisted thoracic surgery (RATS) and video-assisted thoracic surgery (VATS) are the two principal minimally invasive surgical approaches for patients with lung cancer. This study aimed at comparing the long-term and short-term outcomes of RATS and VATS for lung cancer. Methods A comprehensive search for studies that compared RATS versus VATS for lung cancer published until November 31, 2021, was conducted. Data on perioperative outcomes and oncologic outcomes were subjected to meta-analysis. PubMed, Web of Science, and EMBASE were searched based on a defined search strategy to identify eligible studies before November 2021. Results Twenty-six studies comparing 45,733 patients (14,271 and 31,462 patients who underwent RATS and VATS, respectively) were included. The present meta-analysis showed that there were no significant differences in operative time, any complications, tumor size, chest drain duration, R0 resection rate, lymph station, 5-year overall survival, and recurrence rate. However, compared with the VATS group, the RATS group had less blood loss, a lower conversion rate to open, a shorter length of hospital stay, more lymph node dissection, and better 5-year disease-free survival. Conclusions RATS is a safe and feasible alternative to VATS for patients with lung cancer.